Santa Claus is comin' to town ; Year without a Santa Claus [videorecording (DVD)] - Bass, Jules; Marks, Johnny, 1909-1985; Laws, Maury; Pfrimmer, Don; Burgess, Dave, 1934- (Universal Studios, 2023)
Arthur Rankin Jr. and Jules Bass created holiday specials that have been part of Christmas traditions for over 50 years since they were originally broadcast on television. Iconic "Animagic" stop-animation is used in these two timeless tales of Santa Claus.